Artificial Synapse Based on Back‐Gated MoS2 Field‐Effect Transistor with High‐k Ta2O5 Dielectrics. Issue 19 (5th August 2020) - Mohta, Neha; Mech, Roop K.; Sanjay, Sooraj; Muralidharan, R.; Nath, Digbijoy N.
Abstract : Herein, a multilayer MoS2 ‐based low‐power synaptic transistor using Ta2 O5 as a back‐gate dielectric for mimicking the biological neuronal synapse is reported. The use of high‐ k dielectric allows for a lower‐voltage swing compared with using conventional SiO2, thus offering an attractive route to low‐power synaptic device architectures. Exfoliated MoS2 is utilized as the channel material, and the hysteresis in the transfer characteristics of the transistor is exploited to demonstrate excitatory and inhibitory postsynaptic currents, long‐term potentiation, and long‐term depression (LTP/LTD), indirect spike timing‐dependent plasticity (STDP) based on single and sequential gate ( V g ) pulses, respectively. The synapse had achieved a 35% weight change in channel conductance within 15 electrical pulses for negative synaptic gate pulse and 28% change for positive synaptic gate pulse. A complete tunability of weight in the synapse by spike amplitude‐dependent plasticity (SADP) at a low voltage of 4 V is also demonstrated. Abstract : Herein, a synaptic transistor based on a 2D‐MoS2 semiconducting channel and high‐ k Ta2 O5 as an underlining back‐gate dielectric is demonstrated. The use of Ta2 O5 allows the devices to be operated at much lower operating gate voltage with energy consumption of 5 nJ per spike, which makes them a potential candidate for realizing low‐power and energy‐efficient devices for neuromorphic applications.